The Role of PPKn Teachers in Developing Civic Responsibility Among Students at MTs Nahdlatul Mujahidin NW Jempong - Qibthiya Anjani; Mohamad Mustari; Sawaludin (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Education is a cultural subsystem that plays a strategic role in fostering human potential and talent. As the primary facilitator in human resource development, education plays a vital role in both enhancing individual capacity and shaping the nation's strength. In the context of national education, which is based on Pancasila and the 1945 Constitution of the Republic of Indonesia, the learning process is directed at shaping the character of students who are moral, intelligent, and responsible. Teachers, as a crucial component in the educational process, play a central role in instilling national values and civic responsibility in students. The Pancasila and Citizenship Education (PPKn) subject serves as the primary means of fostering citizens who are critical, democratic, tolerant, and aware of social and political responsibility. Instilling civic responsibility in students requires a continuous process through habituation and learning that addresses cognitive, affective, and psychomotor aspects. Therefore, the role of PPKn teachers is very important in guiding students to become good citizens, in accordance with the noble values of Pancasila in social, national and state life. Key Words: Role of PPKn Teachers, Civic Responsibility. Abstrak: Pendidikan merupakan subsistem budaya yang memiliki peran strategis dalam menumbuhkembangkan potensi dan bakat manusia. Sebagai fasilitator utama dalam pengembangan sumber daya manusia, pendidikan berfungsi vital baik dalam meningkatkan kapasitas individu maupun dalam membentuk kekuatan bangsa. Dalam konteks pendidikan nasional yang berlandaskan pada Pancasila dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, proses pembelajaran diarahkan untuk membentuk karakter peserta didik yang berakhlak, cerdas, dan bertanggung jawab. Guru, sebagai komponen penting dalam proses pendidikan, memiliki peran sentral dalam menanamkan nilai-nilai kebangsaan dan civic responsibility kepada siswa. Mata pelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) menjadi sarana utama dalam membina warga negara yang kritis, demokratis, toleran, dan sadar akan tanggung jawab sosial serta politik. Penanaman civic responsibility kepada peserta didik membutuhkan proses yang berkelanjutan melalui pembiasaan dan pembelajaran yang menyentuh aspek kognitif, afektif, dan psikomotor. Oleh karena itu, peran guru PPKn sangat penting dalam membimbing siswa menjadi warga negara yang baik (good citizenship), sesuai dengan nilai-nilai luhur Pancasila dalam kehidupan bermasyarakat, berbangsa, dan bernegara. Kata Kunci: Peran Guru PPKn, Civic responsibility.